Gut microbiota imbalance and colorectal cancer - Gagnière, Johan; Raisch, Jennifer; Veziant, Julie; Barnich, Nicolas; Bonnet, Richard; Buc, Emmanuel; Bringer, Marie-Agnès; Pezet, Denis; Bonnet, Mathilde (World journal of gastroenterology : WJG, 2016)
The gut microbiota acts as a real organ. The symbioticinteractions between resident micro-organisms and thedigestive tract highly contribute to maintain the guthomeostasis. However, alterations to the microbiomecaused by environmental changes （e.g. , infection, dietand/or lifestyle） can disturb this symbiotic relationshipand promote disease, such as inflammatory boweldiseases and cancer. Colorectal cancer is a complexassociation of tumoral cells, non-neoplastic cells and alarge amount of micro-organisms, and the involvementof the microbiota in colorectal carcinogenesis isbecoming increasingly clear. Indeed, many changes inthe bacterial composition of the gut microbiota havebeen reported in colorectal cancer, suggesting a majorrole of dysbiosis in colorectal carcinogenesis. Somebacterial species have been identified and suspectedto play a role in colorectal carcinogenesis, such asStreptococcus bovis , Helicobacter pylori , Bacteroides fragilis , Enterococcus faecalis , Clostridium septicum ,Fusobacterium spp. and Escherichia coli . The potentialpro-carcinogenic effects of these bacteria are nowbetter understood. In this review, we discuss thepossible links between the bacterial microbiota andcolorectal carcinogenesis, focusing on dysbiosis andthe potential pro-carcinogenic properties of bacteria,such as genotoxicity and other virulence factors,inflammation, host defenses modulation, bacterialderivedmetabolism, oxidative stress and antioxidativedefenses modulation. We lastly describehow bacterial microbiota modifications could representnovel prognosis markers and/or targets for innovativetherapeutic strategies.